2005
DOI: 10.1093/rheumatology/kei165
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind trial of depot corticosteroids in Behçet's syndrome

Abstract: Low-dose depot corticosteroids did not have any beneficial effect on genital ulcers. However, it was useful in controlling erythema nodosum lesions, especially among the females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 9 publications
2
34
0
2
Order By: Relevance
“…In a recent double-blind study of low-dose depot corticosteroids vs placebo, low-dose depot corticosteroids (40 mg of methylprednisolone acetate administered as intramuscular injection, every 3 weeks) were not successful in the treatment of genital ulcers, oral lesions and folliculitis and arthritis; however, they were helpful in controlling erythema nodosum lesions, especially in female patients [94].…”
Section: Corticosteroidsmentioning
confidence: 98%
“…In a recent double-blind study of low-dose depot corticosteroids vs placebo, low-dose depot corticosteroids (40 mg of methylprednisolone acetate administered as intramuscular injection, every 3 weeks) were not successful in the treatment of genital ulcers, oral lesions and folliculitis and arthritis; however, they were helpful in controlling erythema nodosum lesions, especially in female patients [94].…”
Section: Corticosteroidsmentioning
confidence: 98%
“…76 Although corticosteroids are widely used for Behçet's syndrome, the only placebo-controlled study with methylprednisolone acetate (40 mg intramuscularly, every 3 weeks) was conducted for genital ulcers. 77 Men and women were analyzed separately. The trial showed that depot corticosteroids were useful only for erythema nodosum lesions among women but not in men, whereas there was no effect on genital ulcers, oral ulcerations, folliculitis, or arthritis.…”
Section: Managementmentioning
confidence: 99%
“…They are reported to be used as first-line drugs for both acute and chronic progressive CNS involvement, for aggressive gastrointestinal lesions and arteritis, for venous thrombosis and uveitis, and as alternative agents in the treatment of persistent mucocutaneous symptoms and arthritis [36,37,Class IV]. There is a single randomized controlled trial with corticosteroid treatment (40 mg intramuscular methylprednisolone depot injections); it showed an effect only on nodular lesions [38,Class I].…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%